2022
DOI: 10.3390/cryst12121721
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Slag Adjustment on Inclusions and Mechanical Properties of Si-Killed 55SiCr Spring Steel

Abstract: The effects of the Al2O3 content and basicity of CaO–SiO2–Al2O3–10 wt.% MgO refining slag on inclusions removal in 55SiCr spring steel were investigated. The viscosity of slag was studied using a viscometer, while the microstructure investigation involved using a water-quenching furnace and a Fourier-transform infrared spectrometer. The influence mechanism of the slag adjustment on inclusions was explored through thermodynamic calculations and kinetic analysis. The results indicated that the viscosity of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The control of inclusions is not only limited to the refining [12][13][14][15][16][17] and solidification processes [18][19][20], but also needs to pay attention to the evolution behavior of inclusions in the hot working process [21]. And in the study of steel samples, it was also found that there are hard, high-melting-point Al 2 O 3 inclusions.…”
Section: Introductionmentioning
confidence: 99%
“…The control of inclusions is not only limited to the refining [12][13][14][15][16][17] and solidification processes [18][19][20], but also needs to pay attention to the evolution behavior of inclusions in the hot working process [21]. And in the study of steel samples, it was also found that there are hard, high-melting-point Al 2 O 3 inclusions.…”
Section: Introductionmentioning
confidence: 99%